Unintended Pregnancy and Associated Factors among Pregnant Women Attending Antenatal Care Unit in Public Health Facilities of Dire Dawa City, Eastern Ethiopia, 2021 - Andinet Ayele; Neil Abdurashid; Mickiale Hailu; Bereket Tefera (Hindawi Limited, 2023)
Background. Unintended pregnancy refers to a pregnancy that is either mistimed or unwanted. Unintended pregnancy has been a troubling public health and reproductive health issue, which imposes appreciable adverse consequences on the mother, child, and the public in general. Globally 121 million unplanned pregnancies occurred from 2015 to 2019. A significant proportion (61%) of these pregnancies ended in abortions each year. In Ethiopia, the challenges of unintended pregnancy and its related complications still exist because of the high rate of unmet need for contraceptives. In addition, no research has been conducted on unintended pregnancy among pregnant women in Dire Dawa city administration. Objective. To determine the prevalence of unintended pregnancy and associated factors among pregnant women attending antenatal care public health facilities in Dire Dawa in 2021. Methods. A facility-based cross-sectional study was conducted. After being chosen randomly, 382 pregnant women were interviewed at 9 urban public health facilities. A pretested questionnaire was used to collect data, entered into Epi Info 7, and exported into SPSS version 25 for analysis. The variables, which were significant at P≤0.25 in bivariate analysis, were included in multivariable analysis. Statistical significance was declared at a P value <0.05 and a 95% CI. Results. In this study, the prevalence of unintended pregnancy was 23.8% at 95% CI (19.8-28.3). The following factors were associated with unintended pregnancy: single women (AOR = 10.93, 95% CI 3.65-32.74), low family income (2000 ETB) (AOR = 4.01, 95% CI 1.73-9.28), parity 3 (AOR = 10.3, 95% CI 4.07-25.84), no history of family planning use (AOR = 5.91, 95% CI 2.46-14.21), and husband decision-making role on reproductive health (AOR = 2.956, 95% CI 1.048-8.340). Conclusion and Recommendations. The prevalence of unintended pregnancy was relatively high in this study. Efforts should be made to scale up women's decision-making power on family planning services and give support to empower women economically. There is the need to promote family planning services to minimize unintended pregnancy and to decrease parity and family size.